ANALISIS GAP KINERJA DAN KEPUASAN PASIEN DI INSTALASI FARMASI RUMAH SAKIT UNIVERSITAS SEBELAS MARET - Marwiyati, Vivin; Rahmatillah, Annie (Universitas Duta Bangsa Surakarta, 2024)
Performance measurement using a descriptive case study method. This research is intended to determine the performance of the Sebelas Maret University Hospital Pharmacy Installation. to see the performance achievements that have been made as well as the basis for further performance improvements. This research aims to determine the performance of the Pharmacy Installation at Sebelas Maret University Hospital. This research is a type of non-experimental research with a descriptive evaluative design. Data were obtained retrospectively and prospectively. Data criteria include qualitative and quantitative data. Qualitative data through interviews and direct observation. Quantitative data through questionnaires. Keywords: Performance, Pharmaceutical Installations, Customer Perspective, Growth Perspective and Learning.